Pemanfaatan Aplikasi Kalkulator Fisika untuk Meningkatkan Motivasi Belajar pada Materi Fisika Gerak - Siwi Puji Astuti (Universitas Indraprasta PGRI Jakarta, 2021)
The purpose of this study is to increase students learning motivation using Matlab. The research was carried out on students of the Informatics Engineering study program, Faculty of FTIK, Indraprasta University, PGRI. The population of this study were the 3rd semester Informatics Engineering students in the odd semester of the 2020/2021 school year. The sample taken in the study used purposive sampling technique. The data were collected by calculating the results of the questionnaire on learning motivation using Matlab. Based on the calculation, the score obtained was 80.81%, or it can be said that students who like to study physics with Matlab were 59.8 or rounded up to 60 students out of 74 students, which means 60 students agreed with the use of Matlab software to make students better understand physics material of motion.